Patents on life : religious, moral, and social justice aspects of biotechnology and intellectual property / edited by Thomas C. Berg, Roman Cholij, Simon Ravenscroft. - Berg, Thomas C., 1960-; Cholij, Roman, 1956-; Ravenscroft, Simon, 1985- (Cambridge University Press, 2015)
This volume brings together a unique collection of legal, religious, ethical, and political perspectives to bear on debates concerning biotechnology patents, or 'patents on life'. The ever-increasing importance of biotechnologies has generated continual questions about how intellectual property law should treat such technologies, especially those raising ethical or social-justice concerns. Even after many years and court decisions, important contested issues remain concerning ownership of and rewards from biotechnology - from human genetic material to genetically engineered plants - and regarding the scope of moral or social-justice limitations on patents or licensing practices. This book explores a range of related issues, including questions concerning morality and patentability, biotechnology and human dignity, and what constitute fair rewards from genetic resources. It features high-level international, interfaith, and cross-disciplinary contributions from experts in law, religion, and ethics, including academics and practitioners, placing religious and secular perspectives into dialogue to examine the full implications of patenting life.